Pengelolaan Proyek Teknologi Informasi dalam Pengembangan Sistem Penentuan Jurusan Kuliah Berdasarkan Minat dan Bakat - Diva Auliya Putri (CV Edujavare Publishing, 2024)
This study developed an information technology-based college major recommendation system to assist high school students in selecting majors that align with their interests and aptitudes. Using an Agile project management methodology, the development process included needs analysis, system design, software development, testing, and system implementation. Data was collected through surveys and interviews with students, resulting in a system capable of providing accurate major recommendations. User trials demonstrated that this system improves efficiency and student satisfaction in the major selection process. The project's success highlights the importance of effective IT project management, with further recommendations for integration and additional personalization features.